Genome-wide identification and expression analyses of genes involved in raffinose accumulation in sesame - Jun You (Nature Portfolio, 2018)
Abstract Sesame (Sesamum indicum L.) is an important oilseed crop. However, multiple abiotic stresses severely affect sesame growth and production. Raffinose family oligosaccharides (RFOs), such as raffinose and stachyose, play an important role in desiccation tolerance of plants and developing seeds. In the present study, three types of key enzymes, galactinol synthase (GolS), raffinose synthase (RafS) and stachyose synthase (StaS), responsible for the biosynthesis of RFOs were identified at the genome-wide scale in sesame. A total of 7 SiGolS and 15 SiRS genes were identified in the sesame genome. Transcriptome analyses showed that SiGolS and SiRS genes exhibited distinct expression profiles in different tissues and seed developmental stages. Comparative expression analyses under various abiotic stresses indicated that most of SiGolS and SiRS genes were significantly regulated by drought, osmotic, salt, and waterlogging stresses, but slightly affected by cold stress. The up-regulation of several SiGolS and SiRS genes by multiple abiotic stresses suggested their active implication in sesame abiotic stress responses. Taken together, these results shed light on the RFOs-mediated abiotic stress resistance in sesame and provide a useful framework for improving abiotic stress resistance of sesame through genetic engineering.